Left Atrial Myxoma Presenting as Lateral Medullary (Wallenberg's) Syndrome. (11th November 2019) - Gupta, Simran; Ayala, Ricky; Desai, Aakash; Modi, Viraj I.; Nardino, Robert J.
Abstract : Myxomas are benign, primary tumors of the heart. Atrial myxomas can present with a variety of clinical features including dyspnea, orthopnea, pulmonary edema, and pulmonary or systemic emboli. Constitutional symptoms such as fever and weight loss may also be present. We report the case of a young female presenting with headache, facial numbness, and vertigo, who was found to have a posterolateral medullary stroke secondary to a large left atrial cardiac myxoma.